Kinetic and Equilibrium Adsorption Studies for Removal of Naphthenic Acids Present in Model Mixture of Aviation Kerosene. Issue 1 (2nd January 2017) - Nascimento, Graziele E. Do; Duarte, Marta M. M. B.; Sales, Deivson C. S.; Barbosa, Celmy M. B. De M.
Abstract : In this work, the adsorbent Sr-MCM-41 was evaluated for its ability to remove naphthenic acids present in model mixture of aviation kerosene (jet fuel) by conducting kinetic and adsorption equilibrium studies in finite bath systems. The adsorption isotherm model of Brunauer, Emmett, and Teller (BET) was used for the equilibrium modeling. Additionally, the linear driving force model was used for the kinetic modeling. The analysis of variance was incorporated to judge the compatibility of the models. The kinetic study found that the system reached equilibrium after 480 min. The equilibrium study showed a maximum adsorption capacity of 2.0 g g −1 . The models represented the experimental data satisfactorily, and this was confirmed by the variance analysis. Under the conditions studied, the presented results show the technical potential of using the adsorbent for the removal of naphthenic acids from jet fuel.